Selection of autolytic lactic acid bacteria as potential adjunct cultures to accelerate ripening of white-brined cheeses - Selime Hazır Dalca; Ömer Şimşek; Oguz Gursoy; Yusuf Yilmaz (Mljekarstvo, 2018)
The aim of this study was to select lactic acid bacteria (LAB) having autolytic activity on the basis of the technological aspects to accelerate the ripening of white-brined cheeses. For this purpose, mesophilic (n=526) and thermophilic (n=413) LAB isolates were collected from 34 raw milk and 16 cheese samples. 27 LAB isolates with a high autolytic activity ranging from 34 to 54 % were identified by (GTG)5 fingerprint and 16S rDNA sequence analyses, which showed that Lactococcus lactis and Enterococcus faecium were abundant among the autolytic isolates in raw milk while E. faecium and Lactobacillus casei were in white-brined cheese. The autolysis rate of LAB strains increased by raising the temperature and pH; however, decreased somewhat at high NaCl concentrations. Additionally, the highest autolysis was observed in the presence of glucose for most of the strains. On the other hand, Lb. plantarum PFC231 was autolyzed differently, being the highest in the presence of lactose. E. durans PFC235, E. faecium PFC232 and Lb. plantarum PFC231 were autolyzed more than other LAB strains, when exposed to low pH, high NaCI concentration at 10 °C simultaneously. However, only Lb. plantarum PFC231, Leuconostoc mesenteroides PFC234, Lc. lactis subsp. cremoris PFC233, Pediococcus acidilactici PFC237 and Lb. rhamnosus PFC238 were able to show intracellular caseinolytic activity. In conclusion, Lb. plantarum PFC231 has the potential to be used as an adjunct starter culture in the production of white-brined cheeses because of its autolysis at low temperature, pH and high salt concentrations, as well as intracellular caseinolytic activity.